1993
DOI: 10.1200/jco.1993.11.8.1523
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea versus misonidazole with radiation in cervical carcinoma: long-term follow-up of a Gynecologic Oncology Group trial.

Abstract: In summary, these data provide stronger evidence than our previous analysis that hydroxyurea is superior to misonidazole as an adjunct to radiation therapy. For patients with locally advanced carcinoma of the cervix, hydroxyurea continues to be the adjunct of choice with radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Our late morbidity rate (10%) is comparable to those reported in other studies patients completed chemotherapy according to protocol. The late morbidity rate in this study was 12% (7/60), 2 of which [2,12,21,35].…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Our late morbidity rate (10%) is comparable to those reported in other studies patients completed chemotherapy according to protocol. The late morbidity rate in this study was 12% (7/60), 2 of which [2,12,21,35].…”
Section: Toxicitymentioning
confidence: 99%
“…No treatment-related deaths occurred. Conclusion: Con-pared with patients treated by pelvic radiation alone, most comitant CDDP/RT is a safe and tolerable method of treating centers have not accepted it as the standard of care [10][11][12]. patients with locally advanced squamous cell carcinoma of the Concomitant radiation/hydroxyurea has, however, become a cervix.…”
Section: III and 25% For Stage Iv The Disease-free Survival At 5 Yearsmentioning
confidence: 99%
“…26,27 The combination of cisplatin and 5-fluorouracil has also been used as concurrent chemotherapy. They are both radiosensitisers and are associated with reduced disease progression and a longer period of disease remission.…”
Section: Stages Iib-iva (Parametrial Extension Up To Lesions Involvinmentioning
confidence: 99%
“…With a central recurrence, exenterative surgery in carefully selected women could give a 5-year survival of 40-60%. 27,30 If there is recurrence after surgery, the usual treatment is radiotherapy with or without platinum-based chemotherapy. The role of chemotherapy is mainly for palliation to relieve symptoms as well as to prolong survival.…”
Section: Recurrent Cervical Cancermentioning
confidence: 99%
“…The Radiation Therapy Oncology Group tested misonidazole as a hypoxic cell-sensitizer in a randomized trial; no improvement in survival was observed [2]. The Gynecology Oncology Group compared hydroxyurea vs. misonidazole with no improvement in survival [38].The Medical Research Council Working Party on advanced carcinoma of the cervix ran another randomized trial with Ro 03-8799 (pimonidazole) as a hypoxic cell-sensitizer. They observed no bene®t by adding pimonidazole to radiotherapy, and a truly adverse effect of the drug was a possible cause of failure in this trial [7].…”
Section: New Approachesmentioning
confidence: 99%